The Development of Prostate Cancer Patients’ information needs: patients’, GPs’ and significant others’ perceptions focusing on diet - Nichols, John; Kassianos, Angelos P.; Raats, Monique (My University, 2013)
The literature provides evi-dence how doctor-patient communication mayimprove health outcomes (Stewart et al., 2000; Becket al., 2002; Flach et al., 2004) especially in cancercare (Mainous et al., 2004). Rees et al. (2003) foundthat prostate cancer patients are highly interested inseeking information. There hasn’t been a studyidentified evaluating the discrepancies betweenhealth professionals, patients and significant othersperceptions as to when patients develop needs inhealth care especially diet